Traumatic rupture of a splenic cyst hydatid - Ozlem, Nuraydin (Int J Surg Case Rep, 2014)
INTRODUCTION: Hydatid cyst (HC) can be observed in all parts of the body, splenic involvement represents 5% of all cases. Many ruptured HC's cases of a primary organ have been reported in the literature. However, only several splenic HC rupture has reported. A patient with traumatic rupture of splenic hydatic cyst is presented. PRESENTATION OF CASE: 37 year old female sustained traffic accident presented our emergency department. In her physical examination there was hemodynamic instability, peritoneal irritation sign. An ultrasonographic examination of her abdomen showed intraperitoneal free fluid, a splenic rupture. The patient urgently operated; a 11 × 9 × 5 cm ruptured HC in the spleen was treated by splenectomy. During surgery the intraabdominal spaces were washed with povidoniodine and saline. Postoperative course of the patient was uneventful. The spleen was an organ involved with hydatidosis in our patient. Pathologic examination of the specimen revealed a splenic hydatid cyst. The patient is symptom free for 18 months. DISCUSSION: Several traumatic ruptured splenic HC case are encountered in the literature. The cases in the literature almost always are not case report but those are one or more than one case in a case series. This case, an extremely infrequent encountered is reporting. CONCLUSION: Early discovery is important since it is possible to cure viable HCs without dissemination to other organs by conservative surgery. If our patient was examined by ultrasound in a routine check up then her hydatid cyst of spleen would be discovered, the treatment of it would be made so no peritoneal dissemination with cystic fluid will be occur.